920. A Sharp Fall in Antibiotic Use in Infants Is Correlated With a Population-Wide Reduction in Asthma Incidence for Children Under 5. (26th November 2018) - Patrick, David; Mamun, Abdullah; Rasali, Drona; Rose, Caren; Marra, Fawziah
Abstract: Background: Antibiotic use in infants <1 is associated with increased relative risk ( 1.5) for childhood asthma in cohort studies. This may be mediated by removal from the infant microbiome of organisms shown to protect against asthma, a hypothesis supported by experiment. We launched this study to see whether reductions in antibiotic use at population level are associated with benefit by way of asthma reduction. Methods: We obtained antibiotic prescribing data from BC PharmaNet, a population-based database that captures all outpatient prescribing for British Columbia, Canada ( n = 4.7 million). We focused on prescriptions in children <1 and calculated prescription rate per 1, 000 population per year. We obtained asthma incidence data from the BC Ministry of Health Chronic Disease Registry. Asthma case identification uses a standard case definition making use of community and hospital diagnostic codes as well as asthma drug data from BC's universal physician billing, hospital and drug databases. We focused on age-stratified asthma incidence for children aged 1–4. The correlation between antibiotic prescription rate in children < 1 and asthma incidence in the following year was estimated using the Spearman test. Results: Antibiotic prescribing for all age groups fell 9.5% between 1999 and 2013. The rate for infants <1 dropped 58% from 1, 014 to 427 prescriptions per 1, 000 population/year. Between 2000 and 2014, asthma incidence (ages 1–4) fell 26% from 27.3 (95% CI: 26.5–28.0) to 20.2 (95% CI: 19.5–20.8) per 1, 000 population/year. These trends were strongly correlated: Spearman's rho = 0.81 ( P = 0.0002). The magnitude of fall in asthma incidence is slightly greater than that predicted based on calculated population attributable risk for antibiotic exposure. Conclusion: The population health benefit from antibiotic stewardship in infants may not be confined to slowing the emergence of resistance and could include a reduced risk of asthma. As this is a population-based ecological study, a reduction in other risk factors may also have contributed to the fall in asthma incidence. This promising trend should be further studied at individual level within a large cohort study. Disclosures: All authors: No reported disclosures.